Phenomenological and Kinetic Aspects of The Thermal Decomposition of Fe(III) Buformin Complex - George, Abraham; C. Nair, Hema (Asian Journal of Chemistry, 2010)
Fe(III) complex of butyl biguanide (buformin) having an octahedral structure has been subjected to thermal analysis. The phenomenological and kinetic aspects of the decomposition have been studied. The Coats-Redfern equation was used for the kinetic studies.